2023
DOI: 10.1038/s41467-023-37690-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genome-wide STR variation in 6487 human genomes

Abstract: Short tandem repeats (STRs) are abundant and highly mutagenic in the human genome. Many STR loci have been associated with a range of human genetic disorders. However, most population-scale studies on STR variation in humans have focused on European ancestry cohorts or are limited by sequencing depth. Here, we depicted a comprehensive map of 366,013 polymorphic STRs (pSTRs) constructed from 6487 deeply sequenced genomes, comprising 3983 Chinese samples (~31.5x, NyuWa) and 2504 samples from the 1000 Genomes Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 130 publications
(253 reference statements)
0
8
0
Order By: Relevance
“…We next examine RE prevalence in coding sequences and regulatory regions (within 5Kb upstream of translation start site), as repetitive elements within these regions can influence gene function and lead to phenotypic diversity (Chuong, Elde, & Feschotte, 2017; Fotsing et al, 2019; Shi et al, 2023). DNA transposons are significantly more abundant in above two regions than retrotransposons (SINEs, LINEs, and LTRs) (p < 0.01; Wilcoxon rank-sum test; Figure 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next examine RE prevalence in coding sequences and regulatory regions (within 5Kb upstream of translation start site), as repetitive elements within these regions can influence gene function and lead to phenotypic diversity (Chuong, Elde, & Feschotte, 2017; Fotsing et al, 2019; Shi et al, 2023). DNA transposons are significantly more abundant in above two regions than retrotransposons (SINEs, LINEs, and LTRs) (p < 0.01; Wilcoxon rank-sum test; Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…We also see that DNA transposons, especially the hAT and hAT.Ac families, are disproportionally found in coding and regulatory regions (Figure 7), consistent with previous studies (Munoz-Lopez & Garcia-Perez, 2010; Wicker et al, 2016; Woodard et al, 2012) We further see a strong positive correlation between transposon activity (insertion and excision) and level of divergence, suggesting that RE movement causes the elevated mutation rates in adjacent sequences (Wicker et al, 2016). Since these transposons are prevalent in functional regions, their mutations likely lead to new functional variants, thereby enhancing the functional complexity required for adaptation to diverse environmental conditions (Chuong et al, 2017; Fotsing et al, 2019; Shi et al, 2023). Therefore, the rapid proliferation of DNA transposons may be a contributing factor to the rapid diversification observed within Gobioidei.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the development of various computational tools, such as Expansion Hunter [ 5 ], has facilitated the reliable detection of repeat expansions in short-read datasets. Recent studies have demonstrated the feasibilities of STR analysis in large-scale short-read genomes or exomes [ 6 11 ]. Therefore, we aimed to explore the diagnostic utilities of STR analysis for identification of pathogenic repeat expansions using exome sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Short DNA repeats constitute ∼3% of the human genome and represent hotspots of genomic instability. Up to now, repeat expansions have been found to cause more than 50 human neurodegenerative diseases. , While the exact molecular mechanism(s) of repeat expansions are far more complex, it has been widely perceived that repeat expansions occur through non-B DNA (e.g., hairpin) formation during replication, transcription, repair, and recombination processes when two complementary DNA strands are transiently separated. , The non-B DNA structure can cause repeat expansions once it escapes from the DNA mismatch repair (MMR) machinery (Figure ). Small-molecule ligands capable of binding to the intrastrand hairpin structure of CAG repeats can reverse trinucleotide repeat expansions in Huntington’s disease, establishing non-B DNA structures as promising druggable targets for developing novel therapeutic strategies. , …”
Section: Introductionmentioning
confidence: 99%